Experimentally manipulating the landscape of fear to manage problem animals. Issue 4 (13th February 2017) - Atkins, Alex; Redpath, Stephen M.; Little, Rob M.; Amar, Arjun
ABSTRACT: Negative interactions between humans and wildlife are increasing, often leading to conflict between different stakeholders over appropriate management interventions. We experimentally tested whether introducing trained Harris's hawks ( Parabuteo unicinctus ) through falconry could be an effective management tool to reduce nuisance Egyptian geese ( Alopochen aegyptiaca ). We hypothesized that falconry would result in elevated fear responses of geese, resulting in increased vigilance, reduced favorability of the site, and locally reduced abundance. We conducted our study on 3 golf courses (1 treatment and 2 controls) in the Western Cape, South Africa, where Egyptian geese are a pest species. Our treatment involved flying the Harris's hawk directly at geese from golf carts. We monitored vigilance and goose numbers before, during, and after treatment. Goose vigilance at the treatment site increased by 76% and abundance declined by 73% following falconry. We did not observe changes at either control site. Although the hawks killed some geese, the decreases in abundance were almost 3 times greater than the numbers killed, indicating that indirect effects were considerably larger than the direct effect of mortality. During the treatment period, vigilance rates were greater in the presence of a golf cart, suggesting that geese learned to associate carts with the threat of predation. Post‐treatment vigilance rates were significantly less than rates detected during the treatment period and goose abundance on the experimental site increased rapidly post‐treatment, returning to pre‐treatment rates within 2 months. Our results demonstrate the efficacy of falconry to reduce nuisance bird abundance and suggest there may be other applications where the deployment of trained predators can be used to mitigate negative human‐wildlife interactions. © 2017 The Wildlife Society. Abstract : We demonstrate the efficacy of falconry to reduce Egyptian geese abundance and highlight the benefits of adopting a mechanistic approach, using knowledge of animal behavior, to develop and apply management tools to solve human‐wildlife conflicts.